ISOLASI, PURIFIKASI DAN KARAKTERISASI Î±-AMILASE DARI Saccharomyces cerevisiae FNCC 3012 - Sari, Dewi Permata (Chem Info Journal, 2013)
Isolation Î±-amylase from Saccharomyces cerevisiae FNCC 3012 were doing to get Î±-amylase that purified by gel filtration chromatograph method and was determined their characteristic like time incubation, pH and optimum temperature. Alpha amylase was god from any step like refresh, growth curve and isolation process using centrifugation. Alpha amylase was produced by Saccharomyces cerevisiae FNCC 3012 was found in fraction 5 in purified process used ammonium sulphate salt in saturated level 80-100% with specific activity 7.28 Unit/mg protein. purification process of Î±-amylase used gel filtration chromatograph used sephadex G-100 was increased specific activity up to 8.56 %. Alpha amylase from Saccharomyces cerevisiae FNCC 3012 have characteristic optimum time incubation before and after purified successively 42 minute and 40 minute, optimum pH 4.9 and optimum temperature is 23ÂºC.